2018
DOI: 10.1039/c7qi00299h
|View full text |Cite
|
Sign up to set email alerts
|

A new class of platinum(ii) complexes with the phosphine ligand pta which show potent anticancer activity

Abstract: The anticancer potential of sixteen platinum(II) complexes with general formulae [PtCl(hq)(S-dmso)] (1a-8a) and [PtCl(hq)(pta)] (1b-8b) (where hq is 5-chloro-7-iodo-8-quinolinol (clioquinol; cqH) (1a, 1b), 8-hydroxy-5-nitroquinoline (nitroxoline; nxH) (2a, 2b), 5,7-dichloro-8-quinolinol (3a, 3b), 5,7-diiodo-8-quinolinol (4a, 4b), 5,7-dibromo-8-quinolinol (5a, 5b), 5,7-dichloro-8-hydroxy-2-methyl-quinoline (6a, 6b), 8-hydroxyquinoline (7a, 7b) and 8-quinolinethiol (8a, 8b); dmso is dimethyl sulfoxide and pta is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 73 publications
3
13
0
Order By: Relevance
“…[27] Other attractive complexes are the neutral [Ru(N-N)-(PTA) 2 Cl 2 ] {N-N = bpy (10), N-N = phen (11)}, monocationic [Ru(N-N)(PTA) 3 Cl]Cl {N-N = bpy (12), N-N = phen(13)} and, di-Scheme 1. [29][30][31] It was showed that the co-ligands bonded to the {Pt(2,2-bpy)} + moiety have a large influence on the reaction kinetics of the complexes with biomolecules such as amino acids, proteins, and DNA. Adapted from ref.…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
See 2 more Smart Citations
“…[27] Other attractive complexes are the neutral [Ru(N-N)-(PTA) 2 Cl 2 ] {N-N = bpy (10), N-N = phen (11)}, monocationic [Ru(N-N)(PTA) 3 Cl]Cl {N-N = bpy (12), N-N = phen(13)} and, di-Scheme 1. [29][30][31] It was showed that the co-ligands bonded to the {Pt(2,2-bpy)} + moiety have a large influence on the reaction kinetics of the complexes with biomolecules such as amino acids, proteins, and DNA. Adapted from ref.…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
“…Complex 11 was found to be the most effective in blocking cell cycle, inducing also necrotic cell death in Multiple Myeloma (MM) cell lines. [31] Scheme 3. Scheme 2.…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
See 1 more Smart Citation
“…Conformation of docked small molecules was analyzed in terms of energy, hydrogen bonding and hydrophobic interaction between the complexes and receptor. The predicted top‐ranking pose with the complexes lowest energy was used to suggest the best possible geometry of the complex inside the receptor (targets) and highest binding affinity between the desired compound (ligand and complexes) and macromolecule . In this study, the binding affinity of the synthesized compounds was performed by Hex 8.0 software against the macromolecules (receptor) of nucleic acid (1BNA) and protein (3hb5), which is an interactive molecular graphics program to understand the drug‐DNA interactions .…”
Section: Resultsmentioning
confidence: 99%
“…Efforts focused on minimizing the toxic effects of metallodrugs in clinical treatment have been substantial in the preclinical field, with metal‐based cancer drugs developing while continuing to mature . From cisplatin to the second‐generation carboplatin and the third‐generation oxaliplatin, all of them have made a significant contribution to the successful treatment of cancer patients .…”
Section: Introductionmentioning
confidence: 99%